Coordinating under incomplete information - Geir B. Asheim; Seung Han Yoo (University of Oslo, Department of Economics, 2007)
We show that, in a minimum effort game with incomplete information where player types are independently drawn, there is a largest and smallest Bayesian equilibrium, leading to the set of equilibrium payoffs (as evaluated at the interim stage) having a lattice structure. Furthermore, the range of equilibrium payoffs converges to those of the deterministic complete information version of the game, in the limit as the incomplete information vanishes. This entails that such incomplete information alone cannot explain the equilibrium selection suggested by experimental evidence.
Keywords: C72; 330; Minimum effort games; Coordination games; Incomplete information; Nichtkooperatives Spiel; Koordination; Unvollkommene Information; Theorie